2013
DOI: 10.1016/j.cplett.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Photo-active and optical properties of bismuth ferrite (BiFeO3): An experimental and theoretical study

Abstract: Publication informationChemical Physics Letters, Publisher Elsevier Item record/more information http://hdl.handle.net/10197/4903 Publisher's statementThis is the author's version of a work that was accepted for publication in Chemical Physics Letters. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 43 publications
6
25
0
Order By: Relevance
“…Undoped BFO is a nearly direct semiconductor with a band gap of 1.1 eV at the PBE level (in good agreement with earlier results) [70]. This, of course, is an underestimation, which can be corrected to give more realistic, larger band gaps via a Hubbard term (reported values of 1.3 -1.9 eV) [71], the inclusion of (screened) exact exchange (reported values of 2.1 -3.6 eV) [72][73][74], or many-body GW calculations (3.6 eV [75]). Experimentally, the optical gap is observed to be of the order of 2.1 -2.8 eV, depending on the exact reaction conditions, phase, and film thickness.…”
Section: A Pristine Bifeo3 and Dopingsupporting
confidence: 86%
“…Undoped BFO is a nearly direct semiconductor with a band gap of 1.1 eV at the PBE level (in good agreement with earlier results) [70]. This, of course, is an underestimation, which can be corrected to give more realistic, larger band gaps via a Hubbard term (reported values of 1.3 -1.9 eV) [71], the inclusion of (screened) exact exchange (reported values of 2.1 -3.6 eV) [72][73][74], or many-body GW calculations (3.6 eV [75]). Experimentally, the optical gap is observed to be of the order of 2.1 -2.8 eV, depending on the exact reaction conditions, phase, and film thickness.…”
Section: A Pristine Bifeo3 and Dopingsupporting
confidence: 86%
“…It has narrow band gap of 2.1 eV with high chemical stability which makes it a very good candidate for visible light responsive photocatalytic material. 15 Perovskite-type of BiFeO 3 demonstrates the coexistence of multiferroic, ferroelectric and antiferromagnetic properties at room temperature with Neel temperature (TN ~367°C) and Curie temperature (TC ~830°C). 16 It has been reported that synthesis of BiFeO 3 @carbon core/shell nanofibres with different thickness of carbon layers were successful and are stable under visible light irradiation and could be easily recycled, indicating that they can be used as effective photocatalysts under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…In any event, this choice of parameters for HSE06-PBEsol is identical to the recent work of Schimka et al [24], who have found that this works well for a range of solids, and also of McDonnell et al [23], both with an exactexchange contribution of 25%. However, it is also possible to change the proportion of exact exchange to tailor the band-gap and optical properties for optimal agreement with experiment; for instance, 10% proportions were used in recent work for bismuth-containing compounds [25,26]. However, the good general agreement between DFT and experiment in this study (vide infra) justifies the choice of 25% exact exchange in this case.…”
Section: Theoretical Methodsmentioning
confidence: 58%